Gaya Arsitektur Kolonial Belanda: Tinjauan Simbolis terhadap Proses Identitas dan Pembentukan Kota di Indonesia - Putri, Aurelya; Adisurya, Rafli; Ichwan, Achmad; Makmalbab, Ibrahim; Maulidya, Aulia; Nurhayati, Eni (Cahaya Ilmu Bangsa Institute, 2024)
This study examines the symbolic meanings embedded in the Dutch colonial architectural style in Indonesia. The primary focus is to understand how architectural elements such as building facades, materials, and ornaments reflect power relations, social identity, and colonial worldviews of the era. Through an in-depth analysis of various colonial buildings across major cities in Indonesia, the research explores how architecture functioned as a political and cultural tool to reinforce colonial dominance while simultaneously influencing the evolution of local and traditional architectural styles in the archipelago. Employing a qualitative approach that includes literature review, interviews with historians and architecture experts, and visual analysis of buildings, this study aims to provide a deeper understanding of colonialism’s impact on Indonesia's architectural landscape. The findings reveal that Dutch colonial architecture represents not only physical structures but also enduring symbols of power, modernity, and Western cultural influence interacting with local traditions.